Reciprocity Aspects of Internationalization Processes for Companies and Markets - Žukauskas, Pranas (Ekonomika, 1998)
The modest aim of the paper is to discuss some of the critical problems in received international marketing research in relation to conceptual framework used by author. More specifically, author examine potential contributions, in terms of problem recognition and research approaches, by looking at markets as networks of relationships between subjects of activities in the market, and between them and objective environment.Because of the cumulative nature of the market activities, the market micro-position (refers to the relationship with a specific individual counterpart) and macro-position (refers to the relations to a network as a whole) are an important concept. At each point in time company has certain positions in the international network. They characterize its relations to other companies, are results of earlier activities in the domestic and international networks both by the firm and other firms, and constitute the base which defines the development possibilities and constrains of the company in the international network.Finally, author discuss how the form's and the environment's internationalization in its different levels interact in analyses of international marketing problems.Theoretical propositions have tasks to help management specify market expansion alternatives for marketing decision making purposes and systematically analyze the problem of choice among the major alternative strategies.